(untitled) (Journal-of-Ethiopian-Church-Studies/የኢትዮጵያ-ቤተ-ክርስቲያን-ጥናት-መጽሔት-Live, 2022)
Monastery (gädam in Amharic) is among the most important institutions of the EOTC. According to the church’s tradition, monasteries and monasticism came to existence with the arrival of the Nine Saints. Ethiopian monasticism becomes more organized and revived in the 13th century through the activities of some well-known monastic figures such as St.Teklehaimanot. This monastic life is either coenobitic (andennat) which stresses communal life style or idiorythemic that allows monks to have private possessions. The objective of the current study is to analyze the kind and nature of narratives which are believed to be created by the founder of Mäkanä Hiwot Mädhane 'Aläm Däbrä Qusqʷam coenobitic monastery, Ǝmmahoy Sahlä Mariyam. The data were collected through open-ended interviews and participatory observations. As the study shows, these narratives are responsible for the establishment of the monastery in 1994 along with two churches. Moreover, more than 42 holy water sites were blessed by the local priests and begun to serve the local community. This new monastery, in which more than 32 monks live, was first established in 2010 as women’s andïnnät gädam. Later in 2011, it became men’s and women’s andïnnät gädam